2024
DOI: 10.1037/pas0001310
|View full text |Cite
|
Sign up to set email alerts
|

Mindreading measures misread? A multimethod investigation into the validity of self-report and task-based approaches.

Leon P. Wendt,
Johannes Zimmermann,
Carsten Spitzer
et al.

Abstract: Mindreading ability-also referred to as cognitive empathy or mentalizing-is typically conceptualized as a relatively stable dimension of individual differences in the ability to make accurate inferences about the mental states of others. This construct is primarily assessed using self-report questionnaires and task-based performance measures. However, the validity of these measures has been questioned: According to rival interpretations, mindreading tasks may capture general cognitive ability, whereas mindread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Finally, this study does not give a response to the question discussed in the introduction, which can be reformulated here as follow: to what extent MMQ assesses people’s mentalizing abilities (and not only their beliefs about their mentalizing abilities)? As discussed recently by Wendt et al [ 25 , p. 9–10], to validated a “mindreading” instrument in terms of assessing “abilities” and not just “beliefs about one’s own abilities”, future studies must go behind the classic tests of internal consistency, structural validity, or convergent validity (with another self-reported measurement instrument), and create task-based assessment tool to be used as “gold standard” to validate a given self-report instrument capacity to assess a set of “real” abilities. In this case, a “gold standard” to validated the MMQ capacity to assess “real” mentalizing abilities must contain tasks in line with the functionalist reconceptualization of mentalizing abilities, that is, mentalizing abilities viewed “in terms of its ecological utility in everyday life, such as the ability to achieve favorable outcomes in interpersonal situations” in which mentalizing is required; appropriated tasks must be designed specifically to go behind inference “of mental states from static information to a broader perspective encompassing interpersonal communication” [ 25 , p. 11–12].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, this study does not give a response to the question discussed in the introduction, which can be reformulated here as follow: to what extent MMQ assesses people’s mentalizing abilities (and not only their beliefs about their mentalizing abilities)? As discussed recently by Wendt et al [ 25 , p. 9–10], to validated a “mindreading” instrument in terms of assessing “abilities” and not just “beliefs about one’s own abilities”, future studies must go behind the classic tests of internal consistency, structural validity, or convergent validity (with another self-reported measurement instrument), and create task-based assessment tool to be used as “gold standard” to validate a given self-report instrument capacity to assess a set of “real” abilities. In this case, a “gold standard” to validated the MMQ capacity to assess “real” mentalizing abilities must contain tasks in line with the functionalist reconceptualization of mentalizing abilities, that is, mentalizing abilities viewed “in terms of its ecological utility in everyday life, such as the ability to achieve favorable outcomes in interpersonal situations” in which mentalizing is required; appropriated tasks must be designed specifically to go behind inference “of mental states from static information to a broader perspective encompassing interpersonal communication” [ 25 , p. 11–12].…”
Section: Discussionmentioning
confidence: 88%
“…The review above shows that, currently, there is several self-reported instruments designed to assess multiple dimensions of mentalizing. Still, many researchers and clinical practitioners [ 22 25 ] continue to express dissatisfaction with the existing self-report instruments, wondering: (a) What do day exactly assess? Do they measure mentalizing ability or a belief about one’s mentalizing abilities?…”
Section: Introductionmentioning
confidence: 99%
“…A range of other RF assessment methods have therefore been developed, primarily self-report measures, intended to reduce administration time and increase applicability (11)(12)(13)(14)(15)(16)). However, the validity of self-report measures has been questioned (17), and several potential limitations of self-report measures has been emphasized, including lack of meta-perspective, social desirability bias, and possibilities of misinterpretation of the questions (14,18). In patients with personality disorders (PDs) characterized by egosyntonic traits and significant impairments in self-reflexivity, scores based on self-report can be even more challenging to the validity of inferences (19).…”
Section: Introductionmentioning
confidence: 99%